The effectiveness of marketing communication tools used by Adabi Consumer Industries Sdn Bhd Rawang in creating brand equity / Norhaslia Hassan - Hassan, Norhaslia (Faculty of Business and Management, 2006)
A brand with strong brand equity is a very valuable asset. Measuring the actual equity of a brand name is difficult. The consumers who trust and display loyalty toward a brand are willing to try to adopt brand extension. Thus, this study is undertaken to examine what are the pertinent factors that lead to the existing problem. It focuses on the effectiveness of marketing communication tools that were used by Adabi Consumer Industries Sdn Bhd in creating brand equity among their customers. The data for this study is sourced from questionnaires distributed to 80 respondents which were taken randomly in Rawang. A set of questionnaires is designed according to research objectives of this study and consists of 61 items.